A first contribution to lichens and lichenicolous fungi of the Nature Reserve “Gorgany” (Ukraine) (CHORNOMORSKI BOTANICAL JOURNAL, 2016)
The first data about 183 species of lichens and 17 species of lichenicolous fungi of Nature Reserve “Gorgany” (Ukraine) are given. Abrothallus usneae Rabenh. is a new for Ukraine, and species Homostegia piggotii (Berk. & Broome) P. Karst., Lichenostigma gracile Calat., Nav.-Ros. & Hafellner, Micarea cinerea (Schaer.) Hedl., Sphaerellothecium parmeliae Diederich & Etayo, Stigmidium fuscatae (Arnold) R. Sant., Tephromela grumosa (Pers.) Hafellner & Cl. Roux are new for Ukrainian Carpathians. The locations, ecology and notes to each species are presented.
Keywords: locations, spruce primeval forests, Carpathians.